2020
DOI: 10.1055/s-0040-1721151
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pooled Serum Internal Quality Control in Comparison with Commercial Internal Quality Control in Clinical Biochemistry Laboratory

Abstract: Introduction With increasing automation in clinical laboratories, the requirements for quality control (QC) material have greatly increased in order to monitor performance. The constant use of commercial control material is not economically feasible for many countries because of nonavailability or the high-cost of those materials. Therefore, preparation and use of in-house QC serum will be a very cost-effective measure with respect to laboratory needs. Materials and Methods In-house internal quality control fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…This study demonstrated significant stability in in-house quality control material stored at −20 °C to −30 °C over eight months, evidenced by consistently lower variability in glucose measurements compared to other storage temperatures. These findings align with previously published data by Sweta et al [ 27 ], Eliezer et al [ 28 ], Andrea et al [ 29 ], and Berhanu et al [ 30 ], solidifying the potential of frozen storage for maintaining QC material integrity. The use of in-house pooled serum, prepared separately, has been identified as a viable alternative to conventional control materials in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated significant stability in in-house quality control material stored at −20 °C to −30 °C over eight months, evidenced by consistently lower variability in glucose measurements compared to other storage temperatures. These findings align with previously published data by Sweta et al [ 27 ], Eliezer et al [ 28 ], Andrea et al [ 29 ], and Berhanu et al [ 30 ], solidifying the potential of frozen storage for maintaining QC material integrity. The use of in-house pooled serum, prepared separately, has been identified as a viable alternative to conventional control materials in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…Khatri et al 16 has shown in their study by using the patient sample that the reliability and validity of test reports will be better when compared to commercial quality control. Kulkarni S et al 17 in their study reported that in house pooled quality control efficacy is better than commercial quality control. Hence in our study, we found that in-house QC can be used for hormone assay also.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, research by Haile B et al (2020) states that pooled sera is a good substitute for commercial serum, especially for developing countries. The same thing was also expressed by Kulkarni, Pierre & Kaliaperumal (2020), that internal Quality Control (QC) made from collected sera is better than commercial internal QC. Therefore, laboratory examination plays an important role in establishing a diagnosis, especially accuracy in triglyceride examination.…”
Section: Introductionmentioning
confidence: 98%